GESTA HERÓICA, OCULTAMIENTO HISTÓRICO E IDENTIDAD DE CLASE. LA PRENSA COSTARRICENSE Y EL 1° DE MAYO (1858-1913) - Urbina Gaitán, Chester (Universidad de Costa Rica, 2015)
The celebration of May Day in Costa Rica during the period 1858-1913 went through differentstages: first was linked to the restoration of the Central American Union, then wasforgotten by the national press, then ligated to the exaltation of the National Campaignand national disgrace that came with the shooting of Juan Rafael Mora and General JoséMaría Cañas. From 1913 Intellectuals linked to the Germinal Center presented the celebrationof May